The healing quilt - Brunstetter, Wanda E. (Uhrichsville, Ohio : Shiloh Run Press, an imprint of Barbour Publishing, Inc., 2014)
"Join retired Amish newlyweds Emma and Lamar Miller in Florida for the winter as they lead another quilting class with a new group of unlikely students: Jennifer, a pregnant new mom; Mike, a charter boat owner; Erika, a wheelchair-bound teen; Kim, a waitress; Noreen, a newly- retired widow, and BJ, an artist facing illness. When old friends visit from Indiana, will romance also become a subject of class discussions?"--Amazon.com.
"Return of the half-stitched Amish quilting club"--Cover.
Includes discussion questions.
Keywords: Amish -- Fiction; Retirees -- Fiction; Newlyweds -- Fiction; Quilting -- Fiction; Sarasota (Fla.) -- Fiction; Florida -- Fiction; Christian fiction